CHANGES IN PLATELET HEMOSTASIS IN POST-COVID SYNDROME (Multidisciplinary Journal of Science and Technology, 2026)
Post-COVID syndrome (also referred to as post-acute sequelae of SARS-CoV-2 infection, PASC) is characterized by persistent, heterogeneous symptoms that may continue for months after the acute infection. A growing body of evidence suggests that dysregulated hemostasis—particularly sustained platelet activation and thromboinflammatory signaling—can persist beyond viral clearance and may contribute to microvascular dysfunction, impaired tissue perfusion, and fluctuating systemic inflammation.